PENGARUH NILAI TUKAR, UKURAN PERUSAHAAN DAN LEVERAGE KEUANGAN TERHADAP PROFITABILITAS (Studi Pada Bank BUMN Yang Terdaftar Di Bursa Efek Indonesia) - Risnaningsih Risnaningsih; Carmelinda Venansia Du Goma; Hendrik Suhendri (Jurnal Akuntansi dan Pajak, 2022)
The purpose of this research is to directly determine the effect of the exchange rate, company size and financial leverage on profitability in state-owned banks as partially registered on the Stock Exchange. This research uses a quantitative descriptive method. In this research, the sample that will be used is a total sample of 4 State-Owned Enterprises banks that have been registered on the IDX. In this research, it is like using a financial report from 2014-2021. The data analysis technique that will be used is using multiple linear regression analysis. The results of this research prove that there is a significant influence on the profitability ratio in State-Owned Enterprise Banks as can be proven based on the Tcount = 3.128, company size can have a significant and significant effect on profitability in State-Owned Enterprise Banks with Tcount = 5,690 and financial leverage has a significant effect on profitability at state-owned banks with t count = 3.486. Banking companies in increasing profitability need to pay attention to financial leverage ratios and company size so that the company value is higher.